AN INVESTIGATION INTO WORDS AND EXPRESSIONS DENOTING TIME IN ENGLISH VERSUS VIETNAMESE: A COGNITIVE SEMANTICS PERSPECTIVE - Ph D. Trần Quang Hải (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
The study is aiming at: Through the cognitive semantics analysis of words and expressions in time in English and Vietnamese, this study is aimed at comparing and contrasting areas of time expressions in order to clarify similarities and differences in the way the Vietnamese and the English apply the expressions of time. The findings of the research are expected to raise potential awareness for both linguistic study and language teaching methodology of the differences in Engl ish-Vietnamese expressions of time in general and the use of its in particular.